1996
DOI: 10.1093/brain/119.5.1633
|View full text |Cite
|
Sign up to set email alerts
|

Executive and mnemonic functions in early Huntington's disease

Abstract: Eighteen patients with early Huntington's disease were compared with age- and IQ-matched control volunteers on tests of executive and mnemonic function taken from the Cambridge Neuropsychological Test Automated Battery. Tests of pattern and spatial recognition memory, spatial span, spatial working memory, spatial planning and visual discrimination learning/attentional set shifting were employed. These tests have previously been found to be sensitive to the later stages of Huntington's disease. Patients with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
209
1
7

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(234 citation statements)
references
References 61 publications
17
209
1
7
Order By: Relevance
“…More work will of course be needed to disentangle these contributions if possible. This hypothesis is compatible with impairments in attention and choice responses in these patients (Bradshaw et al, 1992;Hefter, Homberg, Lange, & Freund, 1987;Jahanshahi et al, 1993;Lawrence et al, 1996). The results are similar to the problems shown by HD patients in the Stroop task, in which an overlearned skill (word reading) interferes with an attention-demanding voluntary response (rapid color naming) (ex: Snowden et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…More work will of course be needed to disentangle these contributions if possible. This hypothesis is compatible with impairments in attention and choice responses in these patients (Bradshaw et al, 1992;Hefter, Homberg, Lange, & Freund, 1987;Jahanshahi et al, 1993;Lawrence et al, 1996). The results are similar to the problems shown by HD patients in the Stroop task, in which an overlearned skill (word reading) interferes with an attention-demanding voluntary response (rapid color naming) (ex: Snowden et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…The EDS is formally equivalent to the category shift in the Wisconsin Card sorting Test. The EDS stage deficit has also been observed in patients with basal ganglia disorders, such as Huntington's disease (Lawrence et al 1996) and in neurosurgical patients with frontal, but not temporal lobe excision (Owen et al 1991). By contrast, the heroin group were less impaired on the EDS stage, although they were more impaired at earlier stages of the test, including the IDS, which involves abstraction and learning set.…”
Section: Discussionmentioning
confidence: 87%
“…At this stage, the subject had to learn that the previously irrelevant dimension was now relevant and the previously relevant dimension was now irrelevant in order to correspond correctly. The EDS stage is equivalent to a category shift in the WCST and has been shown to be sensitive to frontal lobe (Owen et al 1991) and basal ganglia dysfunction (Downes et al 1989;Lawrence et al 1996). The main measures of performance were the stage of the task successfully attained and errors made.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the notion that WM processes are subserved by frontoparietal and striatal areas, WM deficits and frontostriatal dysfunction have also been demonstrated in other disorders of the basal ganglia, e.g., Parkinson's disease [PD] [Altgassen et al, 2007;Lewis et al, 2003;Monchi et al, 2000]. In HD, WM dysfunction is present during early stages of the illness [Lemiere et al, 2004] and has been demonstrated in both patients with manifest HD and individuals with the HD gene mutation who are presymptomatic for the motor symptoms of the disorder [pre-HD individuals] [Lawrence et al, 1996;Montoya et al, 2006;Nehl et al, 2001]. In a sample of pre-HD individuals, we have recently shown aberrant activation of the dorsolateral prefrontal cortex (DLPFC) during WM performance [Wolf et al, 2007b], demonstrating that DLPFC dysfunction may occur several years before the onset of manifest HD symptoms.…”
Section: Introductionmentioning
confidence: 99%